Violence against women: Qualitative research in women victims of intimate partner violence - Valdés Barraza, Pía (2023)
Background: Intimate partner violence is a coercive and/ or controlling behavior on the romantic partner, which includes different types of damage and represents one of the main causes of death for women worldwide. Objective: To describe and interpret the subjective theories about intimate partner violence, of a group of women from a public university in northern Chile, who have been victims of this type of violence in their lives. Method: qualitative methodology, a case study design, and a theoretical sampling of 15 women victims of intimate partner violence, from a university in northern Chile, are used. Fifteen semistructured interviews were applied, which were analyzed based on thematic coding, grounded theory and specific analysis of subjective theories. Results: subjective theories were found that are characterized by promoting the choice of violent partners, keeping women in this type of relationship and protecting self-esteem. Discussion: these results are analyzed in the light of existing theories and suggestions are proposed to address this problem. Authorship contribution PVB, FVM: Research conception and development, article search and selection, theoretical analysis and reflection, analysis and results. DCM: Data analysis, manuscript review, theoretical reflection, writing of results. BMB and BMA: Research development, search and selection of articles and analysis.